Tibet : through the red box - d (New York : Farrar Straus Giroux, 1998)
The author relates his father's experiences while lost in Tibet during the mid-1950s.
"Frances Foster books.".
Wilson's Children, October 2010.
Wilson's Junior High School, January 2010.
Notable/Best Books (A.L.A.), January 1999.
School Library Journal, October 1998.
Book Links (A.L.A.), September 2006.
Keywords: Caldecott honor book; Tibet (China) -- Description and travel -- Juvenile literature; Tibet (China) -- Description and travel; Tibet (China) -- Description and travel; Tibet (China); Tibet (China) -- Description and travel